A Study on Customer Responses to Mobile Banking in Nepalese Development Banks - Poudyal, Dadhiram (Devkota Journal of Interdisciplinary Studies, 2023)
The purpose of this research is to determine how different factors, such as responsiveness, speed, security, and user-friendliness, influence customers’ opinions of mobile banking services offered by Nepali development banks. Combining causal-comparative and descriptive methods, this study investigates how various factors affect customers’ satisfaction levels. A total of 540 people representing 17 different development banks filled out the questionnaires on their own time. When the data was processed, 385 responses were found to be reliable. The results demonstrate a robust and positive connection between these factors and customers’ overall satisfaction. The research highlighted that the security dimension did not significantly affect customer satisfaction. This study will be very helpful for the leadership of Nepalese development banks that are looking to enhance the efficiency of their mobile banking services.